1991
DOI: 10.1002/bbpc.19910950513
|View full text |Cite
|
Sign up to set email alerts
|

Precise Measurements of Second Virial Coefficients of Simple Gases and Gas Mixtures in the Temperature Range Below 300 K

Abstract: A new apparatus for measurements of second virial coefficients of gases or gas mixtures at room temperature is described. It was used to determine virial coefficients of He, H2, N2, CO2, NH3, and the interaction virial coefficient of Ar/NH3. Furthermore, low temperature interaction virial coefficients of Ar/NH3 and H2/CO are reported and finally a critical revision of second virial coefficients of He, H2, Ar, N2, and CO at 77.3 K is presented. The virial coefficients are discussed in their relation to new inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Second virial coefficients for the He-CO interaction have been measured by Brewer 57 and by Schramm et al 58 In the range of temperatures where the measurements overlap, the two data sets are in excellent agreement. Schramm et al measured two additional values at lower temperatures.…”
Section: Interaction Second Virial Coefficientssupporting
confidence: 58%
“…Second virial coefficients for the He-CO interaction have been measured by Brewer 57 and by Schramm et al 58 In the range of temperatures where the measurements overlap, the two data sets are in excellent agreement. Schramm et al measured two additional values at lower temperatures.…”
Section: Interaction Second Virial Coefficientssupporting
confidence: 58%
“…Below 77 K, the first-and secondorder quantum corrections rapidly become more important; we have not compared with the very low temperature data because the first-order angular expansion is probably insufficient there. Figure 1 shows the experimental data of Schramm et al, 13 the values we computed from the SAPT potential, and the values computed by Buck from the potential of Schinke et al 13 The coefficients computed from the Schinke potential are consistently above the experimental data. Those computed from the SAPT potential are consistently below, though the discrepancies are generally smaller.…”
Section: Resultsmentioning
confidence: 63%
“…Several sets of virial coefficient measurements for H 2 -CO are available. 12,13 The more recent ones are a very low temperature set ͑36-60 K͒ calculated by Reuss and Beenakker 14 from the solid-vapor equilibrium data of Dokoupil et al, 15 and a set between 77 and 296 K determined by Schramm et al 13 In this Note we describe the computation of these coefficients from the SAPT potential and compare them to the experimental data.…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8][9][10] Schramm et al determined interaction second virial coefficients for H 2 -CO mixtures. 11 Kudian and Welsh first observed the spectrum of the para-H 2 -CO van der Waals complex in the region of the H 2 stretching fundamental at high density ͑several amagats͒ in a low temperature cell. 12 This work was later extended by McKellar.…”
Section: Introductionmentioning
confidence: 99%
“…By 1984 four different H 2 -CO potential surfaces had appeared. [17][18][19][20] The ''Hartree-Fock ϩdamped dispersion'' potential of Schinke et al 20 was constructed with damping parameters chosen to fit the molecular beam data of Andres et al 4 Though it was later shown not to give good agreement with experimental second virial coefficients 11 or the van der Waals spectra, 15,21 it was the best surface available until recently. Danby et al 21 computed bound levels on the surfaces of Flower et al 18 and Schinke et al 20 and made a preliminary comparison to the infrared spectrum of H 2 -CO. Parish et al 22 reported a ''molecular mechanics for clusters'' study, and Salazar et al 23 reported high-level ab initio calculations for a limited number of nuclear configurations and included a good review of the theoretical work up to 1995.…”
Section: Introductionmentioning
confidence: 99%